RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell

By inserting the RP-phase perovskite nanocrystal layer into the perovskite solar cell, the process is simplified by air environment synthesis, and the environmental stability and defect problems of perovskite solar cell are solved, improving the photoelectric conversion efficiency and stability.

CN119156026APending Publication Date: 2024-12-17HEBEI UNIV OF TECH

Patent Information

Application Number
CN202410831930.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Perovskite solar cells are difficult to develop commercially due to their low intrinsic environmental stability and many defects in the film surface and interface, resulting in low photoelectric conversion efficiency and short service life.

Method used

The RP phase perovskite nanocrystal layer was inserted into a three-dimensional perovskite solar cell, and the nanocrystals composed of [PbX6]4-octahedral structure and spacer Cs+ were used to directly form RP phase calcium by simplifying the synthesis process in an air environment. Titanium nanocrystals omit complex amine salt treatment steps.

Benefits of technology

The quality of perovskite film is improved, the density of defect states is reduced, the carrier life is extended, the photoelectric conversion efficiency and device stability are significantly improved, and the open circuit voltage and short circuit current density are both improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156026A_ABST
    Figure CN119156026A_ABST
Patent Text Reader

Abstract

The invention relates to an RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell. The basic structure of the solar cell device comprises a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light absorption layer, an RP phase perovskite nanocrystalline layer, a hole transport layer and an electrode. The structural formula of the RP-phase perovskite nanocrystal is Cs2PbX4, wherein X is one or more of halide ions I <->, Br <-> and Cl <->; and the thickness of the film is 0.1-100nm. According to the method, the RP-phase perovskite nanocrystals can be synthesized in the air, the preparation process is simple, the synthesis cost is low, the quality of the RP-phase nanocrystal modified three-dimensional perovskite thin film is improved, the defect state density is reduced, the carrier recombination is reduced, and the photoelectric conversion efficiency of a solar cell device is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of novel semiconductor optoelectronic materials and devices, and specifically relates to an RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell and a preparation method thereof. Background Art

[0002] The continuous consumption of non-renewable energy sources such as coal, oil, and natural gas has led to increasingly serious problems such as global warming and biodiversity loss. People are urgently seeking new energy sources that are widely available, renewable, and pollution-free. Solar energy has attracted people's attention due to its advantages such as abundant production capacity and clean and pollution-free, and the corresponding photovoltaic industry has flourished. Perovskite solar cells have developed rapidly due to the excellent photoelectric properties of perovskite materials, such as high absorption coefficient, direct band gap, and high carrier mobility. Its photoelectric conversion efficiency has increased from 3.8% proposed by Miyasaka et al. to more than 26.1% today in the past decade. It is a new type of solar cell that is expected to replace silicon-based photovoltaics.

[0003] Perovskite solar cells have a high theoretical limit of photoelectric conversion efficiency and great development potential. However, the intrinsic environmental stability of perovskite materials is low. Under the influence of light, moisture, oxygen, thermal radiation, etc., they will undergo phase changes or even decompose, which limits their commercialization process. At the same time, there are a large number of defects at the grain boundaries and surfaces of perovskite films, which are prone to non-radiative recombination and ion migration, affecting the transmission of carriers and reducing the service life of the material. Therefore, surface passivation of perovskites is an effective strategy to improve device stability and photoelectric conversion efficiency.

[0004] Perovskite nanocrystals CsPbX3 (X = Cl, Br, I) have quantum confinement effects because their size is close to or smaller than the exciton Bohr radius. The size of the nanocrystals can be regulated by changing the synthesis temperature. At the same time, the bandgap width of the nanocrystals can be further changed by modifying them by chemical methods. Therefore, they are widely used in the field of solar cells. Patent CN116367565A uses a quasi-two-dimensional perovskite nanocrystal to modify a three-dimensional perovskite film. The method is to prepare CsPbX3 nanocrystals in advance under nitrogen protection, and evenly spin-coat them on the three-dimensional perovskite, and then use a macromolecular organic halogenated amine salt to induce the CsPbX3 nanocrystals to transform into quasi-two-dimensional RP phase perovskite nanocrystals for improving the quality of the perovskite film. However, the synthesis atmosphere conditions of the nanocrystals in this method are harsh, and subsequent amine salt treatment is required, and the process is relatively complicated. Summary of the invention

[0005] The purpose of the present invention is to address the problem that the current three-dimensional perovskite solar cells have a large defect state density, poor device stability and are difficult to commercialize, and propose a strategy for modifying three-dimensional perovskite solar cells with RP phase perovskite nanocrystals. The invention inserts a RP phase perovskite nanocrystal layer between the three-dimensional perovskite light absorption layer and the hole transport layer. The nanocrystal is composed of [PbX6] 4- Octahedral structural unit and spacer ion Cs + The present invention has a simple preparation process and low synthesis cost. The quality of the prepared three-dimensional perovskite film modified with RP phase nanocrystals is improved, the defect state density is reduced, the carrier recombination is reduced, and the photoelectric conversion efficiency of the solar cell device is significantly improved.

[0006] The technical solution of the present invention is:

[0007] A RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell, the basic structure of which includes a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light absorption layer, an RP phase perovskite nanocrystal layer, a hole transport layer, and an electrode.

[0008] The three-dimensional perovskite light absorption layer is an APbX3 structure; wherein the A position is a cesium ion (Cs + ), methylamine cation (MA + ), formamidinium cation (FA + ) etc.; X is a chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - );Thickness is 200-1000nm;

[0009] The RP phase perovskite nanocrystal structure formula is Cs2PbX4, wherein the X position is a halogen ion I - Br - , Cl - One or more of; thickness is 0.1-100nm;

[0010] The transparent conductive substrate is preferably one or more of fluorine-doped tin dioxide (SnO2) conductive glass (FTO), indium tin oxide transparent conductive glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate);

[0011] The electron transport layer is tin dioxide (SnO2), chlorine-doped tin dioxide, titanium dioxide (TiO2), chlorine-doped titanium dioxide, [6,6]-phenyl C 61 At least one of methyl butyrate (PCBM), TiO2-PCBM, SnO2-PCBM, zinc oxide (ZnO), molybdenum trioxide (MoO3), TiO2-SnO2, ZnO-TiO2, and ZnO-SnO2, with a thickness of 10-200 nm;

[0012] The hole transport layer is one or more of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), nickel oxide (NiOx), cuprous iodide (CuI), cuprous thiocyanate (CuSCN), and chromium oxide (Cr2O3), and the thickness of the hole transport layer is 10-300nm;

[0013] The electrode is one or more of carbon, gold, silver, aluminum, chromium and copper; when the electrode is a metal electrode, the thickness is 50-200nm; when the electrode is a carbon electrode, the thickness is 5-200μm.

[0014] The method for preparing the RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell comprises the following steps:

[0015] 1) preparing an electron transport layer on a cleaned and dried transparent conductive substrate;

[0016] 2) Spin coating a three-dimensional perovskite precursor solution with a target component of APbX3 on the electron transport layer using a coating machine, and then annealing the solution after treatment with a low-pressure auxiliary device to obtain a three-dimensional perovskite layer;

[0017] The solvent of the three-dimensional perovskite precursor solution includes one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile (ACN), dimethylacetamide (DMAc), γ-butyrolactone, methylamine formate, methylamine acetate, methylamine butyrate, and methanol, and the concentration of lead ions in the precursor solution is 0.5-2 mol / L;

[0018] 3) Spin coating the RP phase perovskite nanocrystal solution on the surface of the three-dimensional perovskite layer: spin coating the RP phase perovskite nanocrystal on the upper surface of the three-dimensional perovskite, and annealing at 70-200° C. for 30 seconds to 30 minutes;

[0019] Wherein, the concentration of the RP phase perovskite nanocrystal solution is 0.1-10 mg / mL.

[0020] The method for preparing RP phase perovskite nanocrystals comprises the following steps:

[0021] Put the halide precursor in an oil bath and heat it to 160-170°C, and stir; after 8-12 minutes, put the cesium carbonate precursor in an oil bath and heat it to 145-155°C, and stir; when both are dissolved at the same time, immediately inject the cesium carbonate precursor solution into the halide precursor solution, stir and react for 5-10s, and then cool it to room temperature with ice water to obtain a stock solution of RP phase perovskite nanocrystals, add methyl acetate and centrifuge to remove the long-chain ligands in the nanocrystal stock solution, and finally disperse the RP phase perovskite nanocrystals in toluene or n-hexane to obtain a RP phase perovskite nanocrystal solution;

[0022] The solvents of the halide precursor solution and the cesium carbonate precursor solution are mixed solvents, and the concentrations are 20-25 mg / mL and 10-15 mg / mL respectively;

[0023] The mixed solvent in the cesium carbonate precursor solution is composed of octadecene and oleic acid, and the volume ratio of the two is 8:1;

[0024] The mixed solvent in the halide precursor solution is composed of octadecene, oleic acid and oleylamine, and the volume ratio of the three is 40:1:4;

[0025] 4) preparing a hole transport layer on the upper layer of RP phase perovskite nanocrystals;

[0026] 5) A metal electrode is prepared on the surface of the hole transport layer by thermal evaporation, or a carbon electrode is prepared by blade coating.

[0027] The essential features of the present invention are:

[0028] Relevant studies have found that devices made of three-dimensional perovskites have a large number of defects on the film surface or interface, which affects the photovoltaic performance of perovskite devices. In current technology, the use of perovskite nanocrystals to modify the surface of three-dimensional perovskites plays a certain passivation role, but in the typical hot injection method to synthesize zero-dimensional CsPbX3 nanocrystals, it is usually necessary to use protective gas to prevent the precursor solution from oxidizing under heating conditions, or to post-treat zero-dimensional perovskite nanocrystals with amine salts to obtain stable RP phase nanocrystal-modified perovskite solar cells, and the synthesis process is complicated.

[0029] The synthesis of RP phase perovskite nanocrystals in the present invention can be achieved in air by precisely controlling the heating and dissolving sequence and time interval of the halide precursor and the cesium carbonate precursor to ensure that the two are dissolved at the same time and then quickly hot injected. The synthesized nanocrystals can be placed in the air for one month without undergoing obvious phase change.

[0030] The reason why the RP phase nanocrystals of the present invention can be directly synthesized in air is as follows: ① The RP phase nanocrystals are composed of [PbX6] 4- Octahedral structural unit and spacer ion Cs + 1. The cesium carbonate precursor and halide precursor required for synthesizing nanocrystals are easily oxidized when heated and dissolved in the air, and the halide precursor has a longer dissolution time than the cesium carbonate precursor. Therefore, the present invention controls the heating and dissolving sequence and time interval of the two precursors so that they are dissolved just at the same time before hot injection, shortening the time that the two precursor solutions are exposed to the air, thereby realizing synthesis in the air. Compared with the prior art of using quasi-two-dimensional RP phase perovskite nanocrystals to modify three-dimensional perovskites, the process of pre-synthesizing zero-dimensional perovskite nanocrystals and post-treatment of amine salts is omitted, and the synthesis process is simpler and the cost is lower. At the same time, the synthesized RP phase perovskite nanocrystals have longer carrier lifetimes, higher environmental stability and lower defect state density. The anions and cations in the nanocrystals can enter the lattice of the three-dimensional perovskite through ion diffusion, filling vacancies while reducing defects on the surface of the perovskite. In addition, since the RP phase perovskite nanocrystals act on the upper interface of the three-dimensional perovskite, the energy level is more matched with the hole transport layer, further improving the photoelectric conversion efficiency and stability of the solar cell device.

[0031] The beneficial effects of the present invention are:

[0032] The preparation method of the RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell described in the present invention is simpler and has lower cost than the process of conventional zero-dimensional CsPbX3 nanocrystal modified solar cell. It can effectively passivate defects in the three-dimensional perovskite, reduce the roughness of the film surface, facilitate good contact between device interfaces, optimize carrier transport capabilities, and at the same time better match the energy level of the hole transport layer.

[0033] Compared with the unmodified device, the open circuit voltage of the device modified with RP phase perovskite nanocrystals increased from 1.09V to 1.16V, and the short circuit current increased from 24.88mA / cm 2 Increased to 25.64mA / cm 2, while the open circuit voltage of the device modified with zero-dimensional perovskite nanocrystals increased to 1.13V, and the modification effect on the device was limited. From the perspective of device efficiency, the photoelectric conversion efficiency of the unmodified three-dimensional perovskite device and the device modified with zero-dimensional perovskite nanocrystals were 21.61% and 22.77%, respectively, but the device modified with RP phase perovskite nanocrystals can achieve a maximum photoelectric conversion efficiency of 23.87%, and the modification effect on the device is more significant. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the structure of the perovskite solar cell described in the present invention; wherein 1 is a transparent conductive substrate, 2 is an electron transport layer, 3 is a three-dimensional perovskite light absorption layer, 4 is an RP phase perovskite nanocrystal, 5 is a hole transport layer, and 6 is an electrode.

[0035] Figure 2 This is a transmission electron microscopy image of the zero-dimensional CsPbCl3 perovskite nanocrystal in Comparative Example 3.

[0036] Figure 3 This is a high-resolution transmission electron microscopy image of the zero-dimensional CsPbCl3 perovskite nanocrystals in Example 3.

[0037] Figure 4 This is a scanning transmission electron microscopy image of the RP phase Cs2PbI2Cl2 perovskite nanocrystals in Example 1.

[0038] Figure 5 This is a high-resolution scanning transmission electron microscopy image of the RP phase Cs2PbI2Cl2 perovskite nanocrystals in Example 1.

[0039] Figure 6 This is the X-ray diffraction pattern of the RP phase Cs2PbI2Cl2 perovskite nanocrystals prepared in air and nitrogen atmospheres in Example 1.

[0040] Figure 7 is the FA prepared in Comparative Example 2 0.85 MA 0.15 Scanning electron microscopy image of the top surface of a 3D perovskite film of PbI3.

[0041] Figure 8 The FA modified by zero-dimensional CsPbCl3 perovskite nanocrystals in Example 3 0.85 MA 0.15 Scanning electron microscopy image of the top surface of a PbI3 perovskite.

[0042] Fig. 9 The FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystal in Example 1 0.85 MA 0.15Scanning electron microscopy image of the top surface of a PbI3 perovskite film.

[0043] Fig.10 is the FA prepared in Comparative Example 2 0.85 MA 0.15 JV curve of PbI3 three-dimensional perovskite solar cells.

[0044] Fig.11 The FA modified by zero-dimensional CsPbCl3 perovskite nanocrystals in Example 3 0.85 MA 0.15 JV curve of PbI3 perovskite solar cells.

[0045] Fig.12 The FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystal in Example 1 0.85 MA 0.15 JV curve of PbI3 perovskite solar cells. DETAILED DESCRIPTION

[0046] The examples listed below can enable workers in this research direction to have a more comprehensive understanding of the present invention, but the examples of the present invention are not limited to those described below.

[0047] Example 1.

[0048] FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystals 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cell, the schematic diagram of the device structure is shown in Figure 1 As shown, from bottom to top are a transparent conductive substrate 1, an electron transport layer 2, a three-dimensional perovskite light absorption layer 3, an RP phase perovskite nanocrystal layer 4, a hole transport layer 5, and an electrode 6. The specific preparation process is as follows:

[0049] Step 1: Cleaning the fluorine-doped tin dioxide (SnO2) conductive glass (FTO) substrate:

[0050] Use a glass cutter to cut the 100×100 mm FTO glass into substrates with a size of 20×20 mm, use glass cleaner, deionized water, and anhydrous ethanol to ultrasonically clean them for 30 minutes, then blow them dry with a nitrogen gun, and place them in a UV ozone box for treatment for 10 minutes.

[0051] Step 2: Preparation of an electron transport layer of polyacrylic acid doped SnO2 (PAA-SnO2):

[0052] Prepare PAA-SnO2 solution: Use a balance to weigh 3 mg of polyacrylic acid (PAA) and dissolve it in 3 mL of deionized water. Oscillate for 30 minutes until it is completely dissolved. Then use a pipette to add 150 μL of 12% SnO2 solution and oscillate for 30 minutes until it is evenly mixed.

[0053] The ozone-treated FTO substrate was placed on a coating machine (KW-4A desktop coating machine), and the dust was blown gently on the surface with an ear-cleaning bulb. 100 μL of PAA-SnO2 was dropped on the surface with a pipette, and spin-coated at 4000 rpm for 30 seconds, followed by annealing at 100°C for 30 minutes. The thickness of the obtained electron transport layer was 50 nm.

[0054] Step 3: Preparation of FA 0.85 MA 0.15 PbI3 three-dimensional perovskite light absorption layer:

[0055] Prepare the perovskite precursor solution: first add 1.02mmol formamidinium iodine (FAI), 0.18mmol methylamine iodine (MAI), 1.2mmol lead iodide (PbI2) and 0.18mmol methylamine chloride (MACl), then add 100μL N-methylpyrrolidone (NMP) and 800μL N,N-dimethylformamide (DMF) as solvent, shake for 30min until completely dissolved, and the concentration of the obtained precursor solution is 1.33mol / L. The concentration is based on Pb 2+ Concentration meter.

[0056] After the annealed glass is cooled to room temperature, it is placed on a coating machine, 60 μL of perovskite precursor solution is dropped on the PAA-SnO2 substrate, and the spin coating is performed for 6 seconds at a speed of 3000 rpm. Then, it is immediately placed in a low-pressure auxiliary system (DL-10A quartz vacuum gauge and vacuum pump) for low-pressure (vacuum degree of 10 Pa) treatment for 30 seconds to allow the solvent to evaporate quickly, thereby obtaining a well-crystallized intermediate phase film. After the low-pressure treatment is completed, annealing is performed on a heating table at 150°C for 15 minutes to obtain a well-crystallized perovskite film. Scanning electron microscopy images are shown in Figure 2. Figure 7 As shown, relatively uniform-sized grains were obtained, there were no obvious holes on the surface of the perovskite film, and the thickness was 450 nm.

[0057] Step 4: Preparation of RP phase Cs2PbI2Cl2 perovskite nanocrystalline layer:

[0058] Prepare FA 0.85 MA 0.15 The glass of PbI3 perovskite was placed on a spunbond, 100 μL of RP phase Cs2PbI2Cl2 perovskite nanocrystals were added using a pipette, and spin-coated at 4000 rpm for 30 seconds, and then annealed on a heating stage at 100 °C for 5 minutes. Scanning electron microscopy images are shown in Figure 2. Fig. 9 As shown in Figure 2, after adding RP phase Cs2PbI2Cl2 perovskite nanocrystals, the three-dimensional perovskite grain size did not change significantly. 0.85 MA 0.15 The presence of white spots on the surface of PbI3 perovskite indicates that the RP phase Cs2PbI2Cl2 perovskite nanocrystals have been evenly coated on the surface with a thickness of 20 nm.

[0059] In this example, RP phase Cs2PbI2Cl2 perovskite nanocrystals were synthesized by hot injection method, and all processes were carried out in air.

[0060] First, place the double-necked flask containing the halide precursor in an oil bath and heat it to 165°C, stirring to accelerate dissolution. After 10 minutes, heat the cesium carbonate precursor to 150°C and stir to accelerate dissolution, so that the two precursors can be dissolved at the same time before hot injection. Take 1.5mL of cesium carbonate precursor solution and quickly inject it into the halide precursor solution. Stir the reaction rapidly for 10s, and quickly place it in an ice water bath and cool it to room temperature to obtain Cs2PbI2Cl2 nanocrystal stock solution.

[0061] Methyl acetate (MAC) was added to the Cs2PbI2Cl2 nanocrystal stock solution at a volume ratio of 1:3 for washing, and the precipitate was retained after centrifugation at 6000rpm for 8min. The precipitate was ultrasonically dispersed using toluene (TOL), and then an equal volume of methyl acetate was added for secondary washing, and the precipitate was retained after centrifugation at 6000rpm for 5min. The precipitate was ultrasonically dispersed again using toluene to obtain RP phase Cs2PbI2Cl2 perovskite nanocrystals.

[0062] Preparation of halide precursor: weigh 83.4 mg of lead chloride and 134.8 mg of lead iodide into a two-necked flask, add 15 mL of octadecene, 0.375 mL of oleic acid and 1.5 mL of oleylamine;

[0063] Preparation of cesium carbonate precursor: weigh 400 mg of cesium carbonate and put it into another two-necked flask, add 15 mL of octadecene and 1.75 mL of oleic acid;

[0064] The scanning transmission electron microscopy image of the RP phase Cs2PbI2Cl2 perovskite nanocrystals used in this example is shown in Figure 4 As shown, Cs2PbI2Cl2 nanocrystals have a regular lamellar morphology, an average thickness of 5nm, and a relatively uniform size. Figure 5 This is a high-resolution scanning transmission electron microscopy image of RP phase Cs2PbI2Cl2 perovskite nanocrystals with a lattice spacing of Due to the difference in radius size between iodine ions and chloride ions, the RP phase structure is formed.

[0065] Step 5: Preparation of hole transport layer Spiro-OMeTAD:

[0066] Prepare the hole transport layer Spiro-OMeTAD precursor solution: weigh 72.3 mg Spiro-OMeTAD on a balance, add 1 mL of chlorobenzene (CB) solvent, 28.8 μL of 4-tert-butylpyridine (tBP), and 17.5 μL of Li-TFSI (520 mg / mL) in sequence to prepare a solution.

[0067] The hole transport layer Spiro-OMeTAD precursor solution was spin-coated on the perovskite layer, with a spin-coating volume of 60 μL, a spin-coating speed of 4000 rpm, and a spin-coating time of 30 s. The thickness of the obtained hole transport layer was 150 nm.

[0068] Step 6: Prepare gold (Au) electrode:

[0069] Place the matching mask and gold particles on a thermal evaporation coating machine, use a mechanical pump to evacuate the vacuum in the coating machine to below 10Pa, and then turn on the molecular pump to further evacuate the vacuum to 5×10 -4 Pa, gradually increase the power until the gold particles melt, open the baffle, and control the evaporation rate to The evaporation thickness is 45 nm.

[0070] In this embodiment, a solar simulator is used to select a K-2400 light source to simulate AM 1.5G lighting to perform a JV test on a three-dimensional perovskite solar cell modified with RP phase Cs2PbI2Cl2 perovskite nanocrystals. Fig.12 As shown in the figure, the photoelectric conversion efficiency of the solar cell is 23.87% from the JV curve, and the open circuit voltage, short circuit current density and fill factor are 1.16V, 25.64mA / cm 2 and 80.33%.

[0071] Example 2.

[0072] FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystals 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cells.

[0073] The other steps are the same as those in Example 1, except that:

[0074] In step 4, the thickness of the RP phase Cs2PbI2Cl2 perovskite nanocrystals is 50 nm.

[0075] Example 3.

[0076] FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystals 0.3 MA 0.7 PbI3 three-dimensional perovskite solar cells.

[0077] The other steps are the same as those in Example 1, except that:

[0078] Step 3 FA 0.3 MA 0.7 0.36 mmol of formamidinium iodide, 0.84 mmol of methylamine iodide, and 1.2 mmol of lead iodide were added to the precursor solution of PbI3 three-dimensional perovskite, and 100 μL of dimethyl sulfoxide and 800 μL of DMF were added as solvents in sequence to obtain 900 μL of perovskite precursor solution.

[0079] Example 4.

[0080] Three-dimensional perovskite solar cells based on RP phase Cs2PbI2Cl2 perovskite nanocrystals modified with FAPbI3.

[0081] The other steps are the same as those in Example 1, except that:

[0082] In step 3, 1 mmol of formamidinium iodide, 1 mmol of lead iodide, and 0.18 mmol of methylamine chloride are added to the precursor solution of FAPbI3 three-dimensional perovskite, and solvents such as 100 μL of NMP and 700 μL of DMF are added in sequence to obtain 800 μL of perovskite precursor solution.

[0083] Example 5.

[0084] Three-dimensional perovskite solar cells based on RP phase Cs2PbI2Cl2 perovskite nanocrystals modified with MAPbI3.

[0085] The other steps are the same as those in Example 1, except that:

[0086] In step 3, the precursor solution of MAPbI3 three-dimensional perovskite specifically includes the solutes 1mmol methylamine iodide and 1mmol lead iodide, and the solvents 750μL DMF and 72μL DMSO are added in sequence to obtain 822μL of precursor solution.

[0087] Example 6.

[0088] Based on RP phase Cs2PbI2Cl2 perovskite nanocrystal modified Cs 0.05 (MA 0.05 FA 0.95 ) 0.95 Pb(I 0.95 Br 0.05 )3D perovskite solar cells.

[0089] The other steps are the same as those in Example 1, except that:

[0090] Step 3 Cs 0.05 (MA0.05 FA 0.95 ) 0.95 Pb(I 0.95 Br 0.05 )3 The precursor solution of the three-dimensional perovskite specifically includes 0.87mmol methylamine iodine, 1mmol lead iodide, 0.22mmol methylamine chloride, 0.89mmol methylamine bromide, and 0.5mmol cesium iodide, and the added solvents are 700μL DMF and 100μL NMP.

[0091] Example 7.

[0092] FA modified by RP phase Cs2PbBr2Cl2 perovskite nanocrystals 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cells.

[0093] The other steps are the same as those in Example 1, except that:

[0094] The preparation method in step 4 is the same, except that 134.8 mg of lead iodide is replaced by 110.1 mg of lead bromide (PbBr2).

[0095] Example 8.

[0096] FA modified by RP phase Cs2PbI2Cl2 perovskite nanocrystals 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cells.

[0097] The other steps are the same as those in Example 1, except that:

[0098] In step 5, the hole transport layer uses poly[bis(4-phenyl)(4-butylphenyl)amine] (Poly-TPD), which specifically includes 20 mg of solute Poly-TPD, 50 μL of CMABr amine salt solution and 1 mL of dichlorobenzene. The spin coating volume is 60 μL, the spin coating speed is 3000 rpm, and the spin coating time is 30 seconds.

[0099] Perovskite solar cell has an active area of ​​0.1 cm 2 .

[0100] Comparative Example 1.

[0101] The X-ray diffraction patterns of RP phase Cs2PbI2Cl2 perovskite nanocrystals synthesized in nitrogen atmosphere and RP phase Cs2PbI2Cl2 perovskite nanocrystals synthesized in air are shown in Figure 2. Figure 6 As shown, it can be seen that the RP phase Cs2PbI2Cl2 perovskite nanocrystals synthesized in the air atmosphere of the present invention are basically consistent with the standard PDF card, and have no obvious difference from the nanocrystals synthesized in the nitrogen atmosphere.

[0102] Comparative Example 2.

[0103] Based on FA 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cells.

[0104] The other steps are the same as those in Example 1, except that:

[0105] There is no step four in the preparation process of perovskite solar cells.

[0106] The prepared perovskite solar cell devices were subjected to JV tests, such as Fig.10 As shown in the figure, the photoelectric conversion efficiency of the solar cell is 21.61% from the JV curve, and the open circuit voltage, short circuit current density and fill factor are 1.09V, 24.88mA / cm 2 and 79.35%.

[0107] Comparative Example 3.

[0108] FA modified by zero-dimensional CsPbCl3 perovskite nanocrystals 0.85 MA 0.15 PbI3 three-dimensional perovskite solar cells.

[0109] The other steps are the same as those in Example 1, except that:

[0110] In step 4, zero-dimensional CsPbCl3 perovskite nanocrystals are used. Specifically, 300 mg of cesium carbonate is weighed and put into a three-necked flask, 15 mL of octadecene and 1.88 mL of oleic acid are added, and the mixture is heated and stirred at 120°C for 30 min under a vacuum environment to react to generate a cesium oleate precursor solution. Then 209.2 mg of lead chloride is put into another three-necked flask, 10 mL of octadecene, 1 mL of oleic acid and 1 mL of oleylamine are added, and the mixture is heated and stirred at 120°C for 30 min under a vacuum environment to form a lead chloride precursor solution. Then, nitrogen is passed through the two three-necked flasks and stored in a nitrogen environment. The lead chloride precursor solution is heated to 165°C, and 1.5 mL of cesium oleate precursor solution is quickly injected into the lead chloride precursor solution, and the mixture is quickly stirred for 10 seconds. The ice bath is cooled to room temperature to obtain a CsPbCl3 nanocrystal stock solution. The subsequent cleaning and centrifugation process is the same as step 4 in Example 1. Its transmission electron microscopy image is as shown in FIG. Figure 2 As shown in Figure 1, the nanocrystal grain size is relatively uniform. Its high-resolution transmission electron microscopy image is shown in Figure 1. Figure 3 As shown, the interplanar spacing corresponding to the (110) crystal plane is The scanning electron microscopy images are as follows Figure 8 As shown, a large number of white spots can be observed on the upper surface and interface of the grains, indicating that the CsPbCl3 perovskite nanocrystals have been evenly spin-coated on the upper surface of the three-dimensional perovskite.

[0111] The prepared perovskite solar cell devices were subjected to JV tests, such as Fig.11 As shown in the figure, the photoelectric conversion efficiency of the solar cell is 22.77% from the JV curve, and the open circuit voltage, short circuit current density and fill factor are 1.13V, 25.01mA / cm 2 and 80.31%.

[0112] The above embodiments illustrate that the three-dimensional perovskite light absorption layer modified with RP phase perovskite nanocrystals can passivate surface defects and improve carrier transport performance. The energy levels of the three-dimensional perovskite layer and the hole transport layer are more matched, which improves the open circuit voltage of the device and increases the photoelectric conversion efficiency from 21.61% to 23.87%, which has a good application prospect in the field of photovoltaic devices.

[0113] The present invention is not limited to the above-mentioned embodiments, and may be varied within the scope of the claims. The above-mentioned embodiments and the description are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

[0114] Matters not covered by the present invention are known technologies.

Claims

1. A RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell, characterized by The solar cell comprises a transparent conductive substrate, an electron transport layer, a three-dimensional perovskite light absorption layer, an RP phase perovskite nanocrystal layer, a hole transport layer and an electrode; The RP phase perovskite nanocrystal structure formula is Cs2PbX4, wherein the X position is a halogen ion I - Br - , Cl - One or more of; thickness is 0.1-100nm.

2. The RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell according to claim 1, characterized in that The three-dimensional perovskite light absorption layer is an APbX3 structure; wherein the A position is a cesium ion (Cs + ), methylamine cation (MA + ), formamidinium cation (FA + ) etc.; X is a chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - );Thickness is 200-1000nm; The hole transport layer is one or more of 2,2',7,7'-tetrakis(diphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), poly-3-hexylthiophene (P3HT), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), nickel oxide (NiOx), cuprous iodide (CuI), cuprous thiocyanate (CuSCN), and chromium oxide (Cr2O3), and the thickness of the hole transport layer is 10-300nm.

3. The RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell according to claim 1, characterized in that The transparent conductive substrate is one or more of fluorine-doped tin dioxide (SnO2) conductive glass (FTO), indium tin oxide transparent conductive glass (ITO), PET / ITO (PET is polyethylene terephthalate), and PEN / ITO (PEN is polyethylene naphthalate); The electron transport layer is tin dioxide (SnO2), chlorine-doped tin dioxide, titanium dioxide (TiO2), chlorine-doped titanium dioxide, [6,6]-phenyl C 61 At least one of methyl butyrate (PCBM), TiO2-PCBM, SnO2-PCBM, zinc oxide (ZnO), molybdenum trioxide (MoO3), TiO2-SnO2, ZnO-TiO2, and ZnO-SnO2, with a thickness of 10-200 nm; The electrode is one or more of carbon, gold, silver, aluminum, chromium and copper; when it is metal, the thickness is 50-200nm, and when it is carbon, the thickness is 5-200μm.

4. The method for preparing a RP phase perovskite nanocrystal modified three-dimensional perovskite solar cell according to claim 1, characterized in that the method comprises the following steps: 1) preparing an electron transport layer on a cleaned and dried transparent conductive substrate; 2) Spin coating a three-dimensional perovskite precursor solution with a target component of APbX3 on the electron transport layer using a coating machine, and then annealing the solution after treatment with a low-pressure auxiliary device to obtain a three-dimensional perovskite layer; The solvent of the three-dimensional perovskite precursor solution is one or more of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), acetonitrile (ACN), dimethylacetamide (DMAc), γ-butyrolactone, methylamine formate, methylamine acetate, methylamine butyrate, and methanol, and the concentration of lead ions in the precursor solution is 0.5-2 mol / L; 3) Spin coating the RP phase perovskite nanocrystal solution on the surface of the three-dimensional perovskite layer: spin coating the RP phase perovskite nanocrystal on the upper surface of the three-dimensional perovskite, and annealing at 70-200° C. for 30 seconds to 30 minutes; in, The concentration of the RP phase perovskite nanocrystal solution is 0.1-10 mg / mL; The method for preparing RP phase perovskite nanocrystals comprises the following steps: Place the halide precursor in an oil bath and heat it to 160-170°C, and stir; after 8-12 minutes, place the cesium carbonate precursor in an oil bath and heat it to 145-155°C, and stir; when both are dissolved at the same time, inject the cesium carbonate precursor solution into the halide precursor solution, stir and react for 5-10 seconds, and then cool it to room temperature with ice water to obtain a stock solution of RP phase perovskite nanocrystals, add methyl acetate and centrifuge to remove long-chain ligands in the nanocrystal stock solution, and finally disperse the RP phase perovskite nanocrystals in toluene or n-hexane to obtain a RP phase perovskite nanocrystal solution; The solvents of the halide precursor solution and the cesium carbonate precursor solution are mixed solvents, and the concentrations are 20-25 mg / mL and 10-15 mg / mL respectively; The mixed solvent in the cesium carbonate precursor solution is composed of octadecene and oleic acid, and the volume ratio of the two is 8:1; The mixed solvent in the halide precursor solution is composed of octadecene, oleic acid and oleylamine, and the volume ratio of the three is 40:1:4; 4) preparing a hole transport layer on the upper layer of RP phase perovskite nanocrystals; 5) A metal electrode is prepared on the surface of the hole transport layer by thermal evaporation, or a carbon electrode is prepared by blade coating.

Citation Information

Patent Citations

  • Quasi-two-dimensional perovskite nanocrystal modified three-dimensional perovskite solar cell

    CN116367565A

Cited By

  • Preparation method of P-SnO2 thin film and application of P-SnO2 thin film in flexible perovskite solar module

    CN120112129A

  • Preparation method of RP phase nanocrystalline modified perovskite solar cell based on ZnCl2 crystal face regulation and control

    CN121888844A